Ethical Behavior and its Relationship to Social Media Uses among Female Students at Preparatory Schools in Baghdad (Journal Of Educational and Psychological Researches, 2023)
The current study aims to assess the ethical behavior among female students who are using a social media network in addition to describe the variables of interest (social media use and ethical behavior) among participants, in which to find out the effects of social media on the ethical behavior of high school female students. A quantitative approach was adopted to collect the relevant data for the study, six schools included in this study from the six directorates of education in Baghdad city. Subsequently, SPSS software was applied to analyze the relevant data of the study. To achieve the research objectives, a questionnaire was composed of three sections: Part I: deals with the student's demographic information. Part II: deals with information about the use of social media, it is a standardized questionnaire. Part III represents the measure of ethical behavior followed by the researcher Issawi in her research prepared by Lee Swanson and Gloria Hill to measure ethical behavior after preparation and Arabization because of the absence of a scale of ethical behavior in Iraqi society. Due to the scarcity of studies on this subject, this scale is developed according to the interpretation of ethical behavior by Kohlberg. The results of the study showed that 73.9 of the study sample have a moderate degree of ethical behavior and there is a relationship between using social media and ethical behavior at the (0.00) level. This study recommended it is necessary to raise the community awareness about the negative effect of social media on adolescent students especially female students in secondary school and increase research in this field.